2002
DOI: 10.1364/ao.41.003187
|View full text |Cite
|
Sign up to set email alerts
|

Design of omnidirectional high reflectors with quarter-wave dielectric stacks for optical telecommunication bands

Abstract: A design for omnidirectional high reflectors with quarter-wave dielectric stacks in the optical telecommunication band that uses conventional optical thin-film design theory is described. The omnidirectional bandwidth is derived in units of wavelength and investigated as a function of its high- and low-refractive-index values in the near infrared. The results show that the high refractive index should be larger than 2.26 for an omnidirectional high reflector and that the low refractive index for maximum onmidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 8 publications
1
47
0
Order By: Relevance
“…They are calculated according to (Kim et. al, 2002) and are presented in The short and long wavelength edges of ODR band can also be expressed explicitly as (Kim et. al., 2002):…”
Section: Short Description Of Theory Of Photonic Crystalsmentioning
confidence: 99%
“…They are calculated according to (Kim et. al, 2002) and are presented in The short and long wavelength edges of ODR band can also be expressed explicitly as (Kim et. al., 2002):…”
Section: Short Description Of Theory Of Photonic Crystalsmentioning
confidence: 99%
“…By rolling into hollow fibers, the mirror can be used as inside walls of high-finesse waveguides and microcavities [22][23][24][25]. They can also be used in coating design, narrow band filters, laser measurements, optical sensors for high precession detection, laser beam security, photovoltaic applications and so on [26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Criterion Of Omnidirectional Reflection In One Dimensional Pmentioning
confidence: 99%
“…In each zone, the wave-function is completely determined by two scalar components; therefore it can be represented as a bi-dimensional (2D) column vector. The linearity of the electromagnetism equations makes possible to relate the components between any two given abscissae z under a (22) matrix form [3]. The transfer matrix of the whole structure is readily expressed as the matrix product:…”
Section: Methodsmentioning
confidence: 99%
“…The omnidirectional reflection properties are mainly dependent on two parameters: the refractive index contrast n H /n L -refractive indices ratio of the layers of high and low refractive index, -and on the ratio of the lower refractive index to the homogeneous medium surrounding the last layers of the stack n L /n A (n A = 1 for air) leading to a photonic band diagram [2]. It was shown that one of the key prerequisite facilitating omnidirectional reflection is: 1) sufficiently high refractive index contrast (>0.8) between the two materials forming thin film stack and 2) high optical transmission of individual materials in wavelength range of interest [1,3]. Due to their suitable properties, amorphous chalcogenide multilayer stacks themselves or combined with low refractive index materials can satisfy mentioned criteria when designing omnidirectional mirrors for infrared region of the spectra.…”
Section: Introductionmentioning
confidence: 99%